Brand Awareness, Brand Image, and Brand Trust on Costumer’s Decisions to Use Sharia-Compliant Pawnshop Products - Iwan Darmawan; Ahmad Firman; Fitriani Latief (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study aims to analyze the influence of brand awareness, brand image, and brand trust on customers’ decisions to use Sharia pawnbroking products at PT Pegadaian Syariah Ujungbulu. Research Method: This study employs a quantitative approach using a survey method involving 102 customers selected through random sampling. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. Results and Discussion: The study indicates that brand awareness and brand image do not significantly affect customer decisions, whereas brand trust has a positive and significant effect. These findings suggest that the decision to use sharia-compliant pawnshop products is influenced more by trust in sharia compliance, contract transparency, and transaction security than by brand awareness or brand image. Implications: This study underscores the importance of building customer trust through consistent adherence to Sharia principles and improving service quality. Originality: This study highlights brand trust as the primary determinant of customer decisions regarding sharia pawnbroking services.